Question:
Answer
Question:
Question:
Question:
Question:১১. প্রমাণ কর: `(4^n - 1)/(2^n - 1) = 2^n + 1`
সমাধান: বামপক্ষ `= (4^n - 1)/(2^n - 1)` `= ((2^2)^n - 1)/(2^n - 1)` `= ((2^n)^2 - 1)/(2^n - 1)` `= ((2^n + 1)(2^n - 1))/((2^n - 1))` [ `:. a^2 - b^2 = (a + b)(a - b)` ] `= 2^n + 1` = ডানপক্ষ `:. (4^n - 1)/(2^n - 1) = 2^n + 1` (প্রমাণিত)
Question:১২. প্রমাণ কর: `(2^(p + 1) .3^(2p - q) .5^(p + q) .6^q)/(6^p .10^(q + 2) .15^p) = 1/50`
সমাধান: বামপক্ষ `= (2^(p + 1) .3^(2p - q) .5^(p + q) .6^q)/(6^p .10^(q + 2) .15^p)` `= (2^(p + 1) .3^(2p - q) .5^(p + q) .(2 xx 3)^q)/((2 xx 3)^p .(5 xx 2)^(q + 2) .(3 xx 5)^q)` `= (2^(p + 1) .3^(2p - q) .5^(p + q) .2^q .3^q)/(2^p .3^p .5^(q + 2) .2^(q + 2) .3^p .5^p)` `= (2^(p + q + 1) .3^(2p - q - q) .5^(p + q))/(2^(p + q + 2) .3^(p + p) .5^(q + p + 2))` `= (2^(p + q + 1) .3^(2p) .5^(p + q))/(2^(p + q + 2) .3^(2p) .5^(p + q + 2))` `= 2^((p + q + 1) - (p + q + 2)) .3^(2p - 2p) .5^((p + q) - (p + q + 2))` `= 2^(p + q + 1 - p - q - 2) .3^0 .5^(p + q - p - q - 2)` `= 2^(- 1) . 1 . 5^(- 2)` `= 1/2 . 1 . 1/5^2` `= 1/2 . 1 . 1/25` `= 1/50` `:. (2^(p + 1) .3^(2p - q) .5^(p + q) .6^q)/(6^p .10^(q + 2) .15^p) ` `= 1/50` প্রমাণিত